EPI-CKD is a poor predictor of GFR in pregnancy. (7th June 2011) - Smith, M C; Moran, P; Davison, J M
Abstract : Background: Estimated glomerular filtration rate (eGFR) is a widespread tool used to screen high risk populations for renal disease. We have previously reported that the Modified Diet in Renal Disease (MDRD) equation is not a clinically useful in pregnancy.1 Recently, Levey et al 2 have published a modification of the previous formula (epi-CKD) to improve prediction at higher filtration rates. Using our previously published data we have evaluated the new equation in pregnancy. Methods: 24 women were serially studied in early and late pregnancy and postpartum. On each occasion GFR was measured using the 'gold standard' method of inulin clearance (Cin ) and this value compared to predicted GFR using the epi-CKD formula. Results: There was no significant difference between Cin and epi-CKD values (p>0.05) in the postnatal period in keeping with the formula being a useful tool in healthy adults outside of pregnancy. Throughout pregnancy, however, the formula significantly underestimated GFR. This was most pronounced in late pregnancy when precision testing as measured by linear regression, yielded an R 2 value of 0.01 and concordance, measured by the Bland-Altman method, was poor with a bias of 40 ml/min/1.73 m 2 . Conclusion: The epi-CKD formula significantly underestimates GFR in pregnancy, similarly to the previously reported MDRD formula. Correlation is poor and the magnitude of discrepancy with actual GFR is such that it would be expected to mislead clinical decisions.